PROMOTION TOURISM WAWOANGI VILLAGE - L.M. Azhar Sa’ban; Ilwan Ilwan; Rosita Rosita (Jurnal Inovasi Penelitian, 2023)
The world of tourism certainly cannot develop and progress if it is not accompanied by promotional activities because only through promotions, prospective tourists both domestic and foreign will be able to know with certainty and more accurately about the destinations or places that they can visit. This study seeks to reveal about how promotion informs the product or service to be offered to potential consumers/tourists who are the target market in Wawoangi Village. Waowangi Village uses promotional media, namely by advertising using print media, electronic media and modern media, namely social media. With a qualitative descriptive method, Wawoangi Village in promotion faces obstacles including budget constraints, infrastructure that is not yet optimal, lack of quality Human Resources (HR). The results of the analysis to overcome promotional obstacles include cooperation with local governments (related agencies), maximizing promotion on social media.